A comparison of quality satisfaction between transactional and relational customers in e-commerce. Issue 6 (7th October 2014) - Yen, Yung-Shen
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to examine quality satisfaction between transactional and relational customers in e-commerce, and it also explores the moderating effect of perceived control and perceived enjoyment on quality satisfaction. Design/methodology/approach – Multivariate analysis of variance and two-way ANOVA were conducted to test the study hypotheses. The samples include 470 university students in the northeastern USA to whom an online survey was administered. Findings – Results show that system quality satisfaction is more significant for transactional customers, but information quality and service quality satisfactions are more important for relational customers. Moreover, perceived control and perceived enjoyment partially moderate quality satisfaction between transactional and relational customers. Research limitations/implications – One limitation is that a student cohort is selected as the sample. This study verifies the understanding of quality satisfaction between transactional and relational customers in e-commerce. Practical implications – Practitioners shall consider the quality of services for fitting different types of customers. While a high-quality system design is better for new customers, high-quality information and service support is helpful for loyal customers. However, if loyal customers have a high degree of perceived control, they may also be more sensitive to system quality satisfaction. Similarly, if new customers have a high degree of perceived control or a high degree of perceived enjoyment, they may be more sensitive to information quality satisfaction. Originality/value – This study contributes to the knowledge regarding quality satisfaction for transactional and relational customers in e-commerce.